Construção identitária, cidadania e religião de egressos do sistema prisional: da transgressão à busca pelo perdão - Barbosa, Maria Eduarda Martins (2023)
This dissertation addresses the construction of identity and citizenship of former prisoners and is part of the research “Egresses from the Prison System: Histories That Matter”, coordinated by Maria Aparecida Penso in the Graduate Program in Psychology at Universidade Católica de Brasília. The theoretical framework is anchored in Psychosociology and Clinical Sociology. The overall objective is to describe how identity supports were configured in the life trajectories of former prison system inmates, explaining the process of constituting the meaning of citizenship. The specific objectives are to know the dynamics of the egress's primary and secondary identity support groups and their contribution in the construction of identity and as a citizen; understand the meaning of the process of constituting the egress's citizenship, pointing out the understanding he has of access to civil, political, and social rights; to analyze the relationship between participation in identity support groups and the meaning of the constitution of citizenship. Its theoretical framework has five thematic axes: the constitution of Brazilian citizenship; identity construction processes and groups of belonging; Brazilian prison system; social exclusion, stigma and disaffiliation; neo Pentecostal religions in Brazil. It is a qualitative and exploratory study, the subjects participating in the research are two men egressed from the prison system of the Federal District. The instrument used was the clinical research interview. Participants' life story narratives were constructed. For data analysis, the clinical method was used. The results are in line with the literature used regarding the displacement of expectations of relationships from the primary group to the secondary group, as well as school dropout as an important risk marker in youth and involvement in criminal activities with the aim of access to consumer goods. Just as it points to the lack of knowledge of rights as a citizen and the attribution of access to public policies as a divine gift from the religious experience, which in turn provides attributes to the subject the symbolic forgiveness that the Prison System refuses to offer. Given the above, it can be concluded that the difficulty of accessing civil and social rights constitutes a risk factor for young people who practice transgression as a strategy for belonging to a group, parallel to the possibility of experiencing access to material goods once unable due to their socioeconomic status. In addition, it is proposed that the way in which the Prison System works, in which the sentence crosses the life history of the ex-prisoners even after their completion, constitutes an excluding element, making difficult personal reorganization and autonomy. This symbolic and material space is sometimes occupied by religious experience, which symbolically forgives the subject and gives other meanings to the breaking of social contracts, as well as creating material conditions for social reintegration. Regarding social belonging in the citizenship axis, the discourse of the Brazilian neo Pentecostal religion in the trajectory of ex-prisoners has, as one of its effects, the significance of the products of social public policies as a divine gift. This meaning has implications for the debate around participatory democracy, because, from the point of view of these subjects, the improvement in their trajectories is the result of divine grace and is linked to the permanence of their conduct in a religious purpose. Thus, in the narrative of these subjects, disputes, struggles and collective mobilization are not perceived as forms of social transformation and guarantee of rights in relations between individuals, groups and the State.